DUA POLA PIKIR MATEMATIKA SEBAGAI TEKNIK MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS IV - Refiana Putricipta Setiono; Triman Juniarso; Pana Pramulia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Two mathematical mindsets are two of four mathematical mindsets integrated into the technique of writing observation report text. The four mathematical mindsets are included as one of the latest writing techniques that were invented by Ayu Utami. This research aimed to determine the influence of two mathematical mindsets on the students’ skill of writing observation report text at grade 4 of SDN Dukuh Menanggal 1 Surabaya. This research utilized a quantitative approach with quasi-experimental posttest-only design. The samples in this research were 4A students as the control team and 4B students as the experiment team. The result of t-test demonstrated that the score of t-count was 9.860 while the score of t-table was 2.0262 at the significance level = 5%  and the degree of freedom = 37. This indicated that t- count (10.794) > t-table (2.0262), so that the hypothesis was accepted. The conclusion of the research was two mathematical mindsets technique significantly influenced the students’ skill of writing observation report text at grade 4 of SDN Dukuh Menanggal 1 Surabaya.